A checklist of the Scarabaeoidea (Coleoptera) of Chile with exemplar live-photographed - Mondaca, José (Zootaxa, 2023)
An updated list of the Scarabaeoidea (Coleoptera) species registered in Chile is given, which includes current names, synonyms, and photographs of live specimens of 88 species. The photographs cover 35% of the species present in the country, with all families represented except for Glaresidae and Ochodaeidae. For each species, the geographical distribution is presented from north to south by administrative regions of the country. For species shared with neighboring countries, the distribution by provinces or departments is indicated, while for those that have a worldwide distribution, the countries, or regions where they have been reported are cited. This list includes species whose presence in continental and insular Chile has been verified and confirmed by studying specimens from collections, excluding all records considered erroneous. The systematic ordering is carried out at the family, subfamily, and tribe level following the current classification of the group; genera and species are presented in alphabetical order. Paranimbus peruanus (Erichson) (Aphodiinae) is recorded for the first time in Chile based on specimens collected in the locality of Visviri (Arica and Parinacota Region). The known distribution is extended for the following species: Allidiostoma landbecki (Philippi), A. simplicifrons (Fairmaire), Archophileurus chaconus Kolbe, Brachysternus germaini (Ohaus), Chiasognathus beneshi Lacroix, Cyclocephala modesta Burmeister, Frickius costulatus Germain, Martinezostes posticus (Germar), Martinezostes ruizi Gutiérrez, Megathopa villosa Eschscholtz, Oogenius chilensis Ohaus, O. kuscheli Gutiérrez, Oryctomorphus maculicollis Guérin-Méneville, Paranimbus zoai Dellacasa, Paranomala undulata peruviana (Guérin-Méneville), Phytholaema fenestra Smith & Mondaca, Tesserodoniella meridionalis Vaz-de-Mello & Halffter, Macrodactylus farinosus Philippi, and Ulata argentina Saylor. Considering the great morphological variability and differences in the color pattern of the integument, Chiasognathus grantii holometallicus Rataj, 2012 and Chiasognathus megalodon Rataj, 2013 are considered new synonyms of Chiasognathus grantii Stephens, 1831. The study of the syntype of Copris punctatissima Curtis, 1844 confirms that this species belongs to the genus Homocopris Burmeister, 1846 and that is not conspecific with H. torulosus (Eschscholtz, 1822), therefore, the combination Homocopris punctatissimus (Curtis, 1844) new combination is established. The study of the syntype of Copris valdiviana Philippi, 1859 confirms that this species is a synonymy of Homocopris torulosus and not of H. puntatissimus. The morphological study of specimens of the genus Germarostes Paulian, 1982 and the comparison with Chilean specimens of Germarostes posticus (Germar, 1843), confirms that this last species really belongs to the genus Martinezostes Paulian, 1982, therefore, the combination Martinezostes posticus (Curtis, 1843) new combination is established. Based on the inconsistencies that exist with the current definition of the subfamily Melolonthinae, and on the results of a previous phylogenetic analysis, Lichniini is elevated to the category of subfamily, placing Lichniinae new status very close to Aclopinae. There are 79 genera, 251 species and 10 subspecies of Scarabaeoidea in Chile, belonging to the families Geotrupidae (three genera, 10 species), Glaresidae (one genus, one species), Hybosoridae (one genus, six species), Trogidae (one genus, 11 species), Lucanidae (nine genera, 31 species, nine subspecies), Ochodaeidae (one genus, one species), and Scarabaeidae (63 genera, 191 species, one subspecies). In addition, Onthophagus pilauco Tello, Verdú, Rossini, & Zunino, 2021, the first fossil scarab from Chile, is included. Approximately 58% of the listed species are endemic to the country, 39% are native to South America and 3% correspond to introduced species with a wide global distribution.